Pesticides in Agriculture and the Environment - Wheeler, Willis B. (CRC Press, 2009)
The arena of pest management has changed dramatically in the past 30 plus years. Pesticides in Agriculture and the Environment is designed to summarize the state of the various aspects of pest management, some of which did not exist a generation ago and all of which have changed dramatically. It does not focus on the chemistry of the various pest management tactics as did White-Stephens’s book. The present volume describes the current status of pesticide issues and those related to the broader topic of pest management. It discusses integrated pest management (IPM) and how it came to be, the current state of risk assessment, biological control techniques, the economics of pest management and pest management legislation, and the current state of analytical methods used by international regulators and offers a state-of-the-art description of the science of environmental fate. It also presents specific issues for pest management on “minor crops,” the current approach and issues related to chemical applicationtechnology, the important issues of resistance of pests to pesticides and management of that resistance, and, ?nally, a look to the future for both pest management chemistry and the state of the pest management industry. The authors of these chapters represent the best expertise in the field.